Assessment of community knowledge, practice, and determinants of malaria case households in the rural area of Raya Azebo district, Northern Ethiopia, 2017 - Tesfay, Kebede (PLoS One, 2019)
BACKGROUND: In Ethiopia malaria is one of the leading causes of outpatient visits and admission. Still, it remains a major cause of morbidity and mortality in the study area. Therefore, this study was aimed to assess the knowledge, practice, and determinant of malaria case households in rural areas of Raya Azebo district, Northern Ethiopia. METHOD: A community-based cross-sectional survey was conducted in the selected villages of Raya Azebo district from January to June 2017. A multi-stage random sampling method was employed to select a total of 422 study households. Data was collected using a semi-structured questionnaire. The household head was interviewed face to face. Logistic regression analysis was used to determine the determinant of malaria cases households. RESULT: A total of 412 (97.6) of the respondents had ever heard about malaria. About 63% of households recognized the causes of malaria to be a mosquito bite. Around 173 (41%) of the study households had been treated for malaria within a year of data collection. This study also revealed that the presence of mosquito breeding sites near to home, bed bug infestation, outdoor sleep due to bed bugs and household with poor bed net practicing were significantly associated with malaria case households. CONCLUSION: Although the overall knowledge on malaria transmission, symptoms, and the preventive measure was relatively good, the rate of household insecticide-treated net coverage and utilization were reported low in the area. Therefore, the distribution of adequate bed net with community-based education is a key intervention to promote household insecticide-treated net utilization. In addition, an effective bed bug management strategy is necessary to overcome the outdoor sleeping habit of the community in the area.